Analisis Maqashid Syariah terhadap Regulasi Cryptocurrency sebagai Alat Pembayaran dan Instrumen Investasi Digital - Rafli Darmawan; Intan Nurrachmi; Liza Dzulhijjah (Bandung Conference Series: Sharia Economic Law)
Abstract. The rapid development of financial technology has positioned cryptocurrency as both a digital payment method and an investment instrument, creating regulatory challenges in Indonesia and Malaysia. This study analyzes the regulation of cryptocurrency in both countries from the perspective of maqashid syariah, focusing on hifz al-mal, maslahah, and mafsadah. The research employs a normative juridical method with statutory and comparative approaches, supported by legal materials, relevant literature, and interviews with Islamic economic law experts from Indonesia and Malaysia. The findings show that both countries reject cryptocurrency as legal tender while allowing it as an investment asset under different legal frameworks. Indonesia classifies cryptocurrency as a tradable commodity under the Financial Services Authority (OJK), whereas Malaysia regulates it as a security under the Securities Commission Malaysia. From the perspective of maqashid syariah, both regulatory approaches seek to protect wealth by balancing the benefits of digital investment with the risks of speculation and volatility. The study concludes that differences in legal classification are the main source of regulatory divergence and recommends that Indonesia strengthen its regulatory framework by considering relevant aspects of Malaysia's model. Abstrak. Perkembangan teknologi keuangan digital menjadikan cryptocurrency sebagai alat pembayaran digital sekaligus instrumen investasi yang menimbulkan tantangan regulasi di Indonesia dan Malaysia. Penelitian ini bertujuan menganalisis regulasi cryptocurrency di kedua negara berdasarkan perspektif maqashid syariah, dengan menitikberatkan pada prinsip hifz al-mal, maslahah, dan mafsadah. Penelitian menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan perbandingan hukum yang didukung bahan hukum, literatur ilmiah, serta wawancara dengan pakar hukum ekonomi syariah dari Indonesia dan Malaysia. Hasil penelitian menunjukkan bahwa kedua negara tidak mengakui cryptocurrency sebagai alat pembayaran yang sah, tetapi memperbolehkannya sebagai instrumen investasi melalui kerangka regulasi yang berbeda. Indonesia mengklasifikasikan cryptocurrency sebagai komoditas di bawah pengawasan OJK, sedangkan Malaysia mengaturnya sebagai sekuritas di bawah Securities Commission Malaysia. Dalam perspektif maqashid syariah, kedua pendekatan tersebut bertujuan melindungi harta dengan menyeimbangkan kemaslahatan investasi digital dan risiko spekulasi. Penelitian ini menyimpulkan bahwa perbedaan klasifikasi hukum menjadi faktor utama yang membedakan regulasi kedua negara serta merekomendasikan penguatan regulasi Indonesia dengan mempertimbangkan aspek model regulasi Malaysia.